2019
DOI: 10.1039/c8fo01663a
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside attenuates isoproterenol-induced mouse myocardial fibrosis through inhibition of the myocardial NF-κB/TGF-β1/Smad signaling pathway

Abstract: Stevioside attenuates isoproterenol-induced mouse myocardial fibrosis, and its mechanisms are associated with the increments of antioxidant ability, PPARγ activation, and Smad7 expression, which cause a synergistic inhibition of the NF-κB/TGF-β1/Smad signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Our result of decreased MDA content by STE supplementation was consistent with the previous finding that STE significantly reversed the lipid peroxidation in the liver of the LPS-challenged rat [49]. Increasing evidence has shown that STE exerts potent antioxidant properties in vivo and in vitro [11,49,51,52]. In agreement with these findings, we also demonstrated that STE markedly increased the total antioxidant capacity, and reduced oxidative stress in the intestinal mucosae of LPS-challenged broilers.…”
Section: Discussionsupporting
confidence: 92%
“…Our result of decreased MDA content by STE supplementation was consistent with the previous finding that STE significantly reversed the lipid peroxidation in the liver of the LPS-challenged rat [49]. Increasing evidence has shown that STE exerts potent antioxidant properties in vivo and in vitro [11,49,51,52]. In agreement with these findings, we also demonstrated that STE markedly increased the total antioxidant capacity, and reduced oxidative stress in the intestinal mucosae of LPS-challenged broilers.…”
Section: Discussionsupporting
confidence: 92%
“…For example, NF-κB can promote the release of TGF-β1 in pulmonary fibrosis [45], whereas inhibition of the TLR4/MyD88/NF-κB pathway can downregulate the expression of TGF-β1 in glomerular mesangial cells [46]. A similar phenomenon was also observed in myocardia, where the activation of NF-κB can lead to an increase in the expression of its downstream target gene TGF-β1 [47]. Therefore, we may infer that PSAP promotes the secretion of TGF-β1 and/or increases the activity of this pathway through the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 74%
“…Canonical TGF‐β signaling mobilizes Smad2 and Smad3 transcription factors that control fibrosis by promoting gene expression . TGF‐β1/Smad2/3 signaling has been shown to contribute to myocardial fibrosis . Overt expression of AP‐1 contributes to volume‐overload‐induced heart failure .…”
Section: Discussionmentioning
confidence: 99%